2014
DOI: 10.1002/admi.201400019
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Shape Memory Effect in Ti‐Ta Thin Films Sputter Deposited at Room Temperature

Abstract: Ti‐Ta based alloys are potential high‐temperature shape memory materials with operation temperatures above 100 °C. In this study, the room temperature fabrication of Ti‐Ta thin films showing a reversible martensitic transformation and a high temperature shape memory effect above 200 °C is reported. In contrast to other shape memory thin films, no further heat treatment is necessary to obtain the functional properties. A disordered α″ martensite (orthorhombic) phase is formed in the as‐deposited co‐sputtered Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…All Bragg reflections were indexed as orthorhombic α″ martensite, space group Cmcm . The possible mechanisms for the formation of martensite in Ti–Ta thin films deposited at room temperature were reported previously . Lattice parameters of the α″ martensite as well as the microstructural information in the as‐deposited film were obtained following a Le Bail pattern fitting procedure of two‐dimensional synchrotron data (Figure b and c).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…All Bragg reflections were indexed as orthorhombic α″ martensite, space group Cmcm . The possible mechanisms for the formation of martensite in Ti–Ta thin films deposited at room temperature were reported previously . Lattice parameters of the α″ martensite as well as the microstructural information in the as‐deposited film were obtained following a Le Bail pattern fitting procedure of two‐dimensional synchrotron data (Figure b and c).…”
Section: Resultsmentioning
confidence: 98%
“…As an example, it has been reported that the addition of up to 3 at% Al (or Sn) to Ti 70 Ta 30 can suppress the ω phase formation and thus improve the functional stability . Ti–Ta alloys have so far been mainly studied as bulk materials, their fabrication as thin films was rarely reported . In thin‐film form, they can be used as high‐temperature micro‐actuators in micro‐electro‐mechanical systems (MEMS).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The martensitic phases also lead to other exotic properties, such as shape memory effects . This memory effect was investigated by Motemani et al in Ti‐Ta coatings produced by magnetron sputtering. Montemani et al results indicated that by using magnetron co‐sputtering, it was possible to obtain the α″ martensitic phase in the as‐deposited room temperature films for Ta contents between 30 and 33 at%.…”
Section: Introductionmentioning
confidence: 99%